International Electron Devices Meeting 2000. Technical Digest. IEDM (Cat. No.00CH37138)
DOI: 10.1109/iedm.2000.904335
|View full text |Cite
|
Sign up to set email alerts
|

Novel high drain breakdown voltage AlGaN/GaN HFETs using selective thermal oxidation process

Abstract: We have developed novel selective thermal oxidation process for AlGaN/GaN Heterostructure Field Effect Transistors (HFETs) and realized extremely high device isolation and high drain breakdown voltage device of over 1OOV The leakage current of device isolation between two active islands exhibited drastic reduction of 5 order of magnitude smaller than that of conventional mesa isolation process. Moreover, the fabricated 1.3um-gatelength AlGaN/GaN HFETs exhibited maximum transconductance ( g m d of 130mS/mm, max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 7 publications
0
6
1
Order By: Relevance
“…Also, it has been suggested that deposition of a thin layer of Al to prior to oxidation improves the uniformity of oxidation. However, the oxidation rate reported there is much higher compared to that of the other reports [6][7][8][9]. No such degradation was obvious from the gate I -V and C -V characteristics obtained in our case.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Also, it has been suggested that deposition of a thin layer of Al to prior to oxidation improves the uniformity of oxidation. However, the oxidation rate reported there is much higher compared to that of the other reports [6][7][8][9]. No such degradation was obvious from the gate I -V and C -V characteristics obtained in our case.…”
Section: Discussioncontrasting
confidence: 67%
“…Thermal oxidation of the barrier AlGaN has also been considered for gate dielectric and device isolation [6][7][8][9]. Large reduction in the leakage current has been reported for selective thermal oxidation isolation over mesa isolation [6]. MOS HEMTs with thermally grown oxide at 900 °C have been reported by Inoue et al [8].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that conventional dry oxidation at 900 C for 60 min forms an approximately 60 nm thick Ga oxide layer on a GaN surface. 10) The oxidation rate obtained by the saturated water vapor treatment at 350 C is higher than the conventional dry oxidation rate at 900 C. This rapid oxidation potential at low temperatures is attributed to the high density of the oxidizer (H 2 O) under the high-pressure condition. As indicated in Table I, the H 2 O density of saturated water vapor is 113.6 kg/m 3 .…”
Section: Resultsmentioning
confidence: 94%
“…12) Besides, by preannealing of AlGaN under the oxidation ambient, the improvement of Schottky barrier height on the AlGaN/GaN heterostructure has been observed by Jeon et al 4) In addition, thermal oxidation process could be a favorable way to achieve the electrical insulation of the AlGaN/GaN heterostructure devices. A selective deep thermal oxidation was proposed by Masato et al 13) to obtain interdevice insulation in the AlGaN/GaN HEMTs, instead of the conventional insulation process, such as dry etching or ion implantation.…”
Section: Introductionmentioning
confidence: 99%